How premium brands should do to upgrade and move to a luxury status: The case of three Portuguese brands that successfully migrated from premium to luxury: Claus Porto, Josefinas and Vila Joya - Câmara, Inês Baptista da (2019)
Premium brands’ upgrade process to luxury is a phenomenon still not well analysed. A literature review allowed assessment of what distinguishes premium and luxury brands. We infered five propositions then tested through a case study research. The research investigated three Portuguese brands that successfully moved from premium to luxury - Claus Porto, Josefinas and Vila Joya. We conclude that acquiring social status is the most essential and difficult feature to deal with, when migrating from premium to luxury as it depends on voluntary and involuntary factors.